Dukungan Metode Waterfall Dalam Merancang Sistem Informasi Pembayaran UKT Universitas Bhayangkara Jakarta Raya - Rafly Fandiansyah; Ahmad Firdaus; Fahrul Bagus Santoso; Ihsan Rahmanda Albar; Luthfi Restu adji; Rizky Ziaul Haq; R Wisnu Prio Pamungkas (Journal of International Multidisciplinary Research, 2024)
Universities are increasingly adapting to changes brought by technological advancements and globalization. Bhayangkara University Jakarta Raya is no different, having implemented an efficient Tuition Payment Information System. This article details the design and development of the system using the waterfall method. The main objective of this system is to make it easier for administrative staff and students to process tuition payments. The research method used a needs analysis approach, consisting of observation and interviews. The waterfall approach was utilized for system implementation. The process involved requirements analysis, system design, implementation, testing and operation. The Unified Modeling Language (UML) served as an object-based system design visualization tool. The tuition payment information system provides login access with divided access rights for students, the Academic Administration Bureau, and the Financial Administration Bureau. The system includes features such as student data management, tuition payment verification, and report preparation. The results of implementation show positive changes in the efficiency and convenience of the tuition payment process for students and administrative staff. This article highlights the role of information systems in improving the efficiency of financial administration and services at Universitas Bhayangkara Jakarta Raya. By allowing students to monitor payments online, the system provides significant support for tuition payment management. Hopefully, this system will contribute positively to improving the quality of educational services at this university, creating efficiency in financial administration, and providing a basis for further development of the information system.   Perguruan tinggi semakin beradaptasi terhadap perubahan yang dibawa oleh kemajuan teknologi dan globalisasi. Universitas Bhayangkara Jakarta Raya juga menerapkan Sistem Informasi Pembayaran Uang Kuliah yang efisien. Artikel ini merinci perancangan dan pengembangan sistem menggunakan metode waterfall. Tujuan utama dari sistem ini adalah untuk memudahkan staf administrasi dan mahasiswa dalam memproses pembayaran uang sekolah. Metode penelitian menggunakan pendekatan analisis kebutuhan yang terdiri dari observasi dan wawancara. Pendekatan waterfall digunakan untuk implementasi sistem. Prosesnya melibatkan analisis persyaratan, desain sistem, implementasi, pengujian dan operasi. Unified Modeling Language (UML) berfungsi sebagai alat visualisasi desain sistem berbasis objek. Sistem informasi pembayaran SPP menyediakan akses aktor login dengan hak akses terbagi untuk mahasiswa, Biro Administrasi Akademik, dan Biro Administrasi Keuangan. Sistem ini mencakup fitur-fitur seperti pengelolaan data siswa, verifikasi pembayaran SPP, dan penyusunan laporan. Hasil implementasi menunjukkan perubahan positif pada efisiensi dan kenyamanan proses pembayaran SPP bagi mahasiswa dan tenaga administrasi. Artikel ini menyoroti peran sistem informasi dalam meningkatkan efisiensi administrasi dan pelayanan keuangan di Universitas Bhayangkara Jakarta Raya. Dengan memungkinkan siswa memantau pembayaran secara online, sistem ini memberikan dukungan yang signifikan untuk manajemen pembayaran uang sekolah. Sistem ini diharapkan dapat memberikan kontribusi positif terhadap peningkatan kualitas layanan pendidikan di universitas ini, menciptakan efisiensi dalam administrasi keuangan, dan memberikan landasan bagi pengembangan sistem informasi lebih lanjut